Games as boundary objects: charting trade-offs in sustainable livestock transformation. Issue 5 (2nd November 2021) - Morris, Joanne; Ensor, Jonathan E.; Pfeifer, Catherine; Marchant, Robert; Mulatu, Dawit W.; Soka, Geofrey; Ouédraogo-Koné, Salifou; Wakeyo, Mekonnen B.; Topi, Corrado
ABSTRACT: Attempts to structurally transform segments of the agri-food system inevitably involve trade-offs between the priorities of actors with different incentives, perspectives and values. Trade-offs are context-specific, reflecting different socio-economic and political realities. We investigate the potential of structured boundary objects to facilitate exposing and reconciling these trade-offs within the context of multi-stakeholder social learning processes with pastoral and mixed crop-livestock communities in Burkina Faso, Ethiopia and Tanzania. Building on boundary objects as items flexible enough to be understood by all without having one common definition, structured boundary objects visualize actors' input in a comparable format to facilitate knowledge sharing. Stakeholders in each country used a simulation tool and board game to explore the implications of changing livestock stocking and management practices for the environment and for actors' future socio-economic priorities. Using structured boundary objects elicited trade-offs between household food and animal feed, and between livestock for income, labour, and/ or cultural functions, reflecting the context-specific and subjective evaluations actors make when attempting to plan livelihood changes. Our findings suggest to policy and decision-makers that sustainable transition plans can be developed when stakeholders in local agri-food systems employ approaches that allow shared understandings of trade-offs inherent to sustainable agriculture to emerge.